Selection of Reference Genes for Quantitative Real-Time RT-PCR Studies in Tomato Fruit of the Genotype MT-Rg1 - González-Aguilera, Karla L.; Saad, Carolina F.; Chávez Montes, Ricardo A.; Alves-Ferreira, Marcio; de Folter, Stefan (Frontiers in Plant Science, 2016)
Quantitative real-time RT-PCR (qRT-PCR) has become one of the most widely used methods for accurate quantification of gene expression. Since there are no universal reference genes for normalization, the optimal strategy to normalize raw qRT-PCR data is to perform an initial comparison of a set of independent reference genes to assess the most stable ones in each biological model. Normalization of a qRT-PCR experiment helps to ensure that the results are both statistically significant and biologically meaningful. Tomato is the model of choice to study fleshy fruit development. The miniature tomato (Solanum lycopersicum L.) cultivar Micro-Tom (MT) is considered a model system for tomato genetics and functional genomics. A new genotype, containing the Rg1 allele, improves tomato in vitro regeneration. In this work, we evaluated the expression stability of four tomato reference genes, namely CAC, SAND, Expressed and ACTIN2. We showed that the genes CAC and Exp are the best reference genes of the four we tested during fruit development in the MT-Rg1 genotype. Furthermore, we validated the reference genes by showing that the expression profiles of the transcription factors FRUITFULL1 (FUL1) and APETALA2c (AP2c) during fruit development are comparable to previous reports using other tomato cultivars.